Longitudinal evolution of non-motor symptoms in early Parkinson’s disease: a 3-year prospective cohort study - Ruwei Ou (Nature Portfolio, 2021)
Abstract The progression of global non-motor symptoms (NMS) in Chinese patients with Parkinson’s disease (PD) has not been explored. We aimed to examine the longitudinal evolution of overall NMS in a 3-year prospective Chinese cohort with early-stage PD. We included 224 patients with early PD who underwent annual evaluation of motor and non-motor symptoms. NMS was assessed using the non-motor symptoms scale (NMSS). We observed an increased number of NMS in the majority of the NMSS domains except mood/apathy and sexual dysfunctions. Significant deterioration was observed in the sleep/fatigue, perceptual problems/hallucinations, attention/memory, gastrointestinal, urinary, and miscellaneous domains during the follow-up (P < 0.05). Notably, the number and the score of sexual dysfunctions decreased with the progression of the disease. All NMSS domains showed a small effect size from baseline to 1-, 2-, and 3-year follow-ups (effect size < 0.5). The generalized estimating equations model indicated that the total number of NMS was significantly associated with age and the Unified Parkinson’s Disease Rating Scale (UPDRS) III score (P < 0.05). Multiple logistic regression indicated that a high number of NMS at baseline was associated with a 3-point, a 6-point, and a 9-point increase in the UPDRS III score from baseline to 1-year (odds ratio [OR] 1.074, P = 0.017), 2-year (OR 1.113, P = 0.001), and 3-year (OR 1.117, P < 0.001), respectively. Our study indicated that overall NMS evolution in early PD is mild and multidimensional; a high NMS burden in early PD predicts the faster motor progression of PD. Our study is helpful for understanding the longitudinal evolution of NMS in PD.